Clinical Outcome after Thrombectomy in Patients with Stroke with Premorbid Modified Rankin Scale Scores of 3 and 4: A Cohort Study with 136 Patients - Seker, F.; Pfaff, J.; Schönenberger, S.; Herweh, C.; Nagel, S.; Ringleb, P.A.; Bendszus, M.; Möhlenbruch, M.A. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: We aimed to analyze the clinical outcome after mechanical thrombectomy in patients with premorbid mRS 3 and 4 because there are currently no data on this patient group.MATERIALS AND METHODS: Between January 2009 and November 2017, all patients with premorbid mRS 3 or 4 undergoing mechanical thrombectomy due to anterior circulation stroke were selected. Good outcome was defined as a clinical recovery to the status before stroke onset (ie, equal premorbid mRS and mRS at 90 days). In addition, mortality at discharge and at 90 days was analyzed.RESULTS: One hundred thirty-six patients were included, of whom 81.6% presented with premorbid mRS 3; and 18.4%, with premorbid mRS 4; 24.0% of patients with premorbid mRS 4 achieved clinical recovery compared with 20.7% of patients with premorbid mRS 3 (P = .788). However, the proportion of hospital mortality and mortality at 90 days was nonsignificant, but markedly higher in patients with premorbid mRS 4. Multivariate analysis identified low NIHSS scores (OR, 0.92; 95% CI, 0.85–0.99; P = .040), high ASPECTS (OR, 1.45; 95% CI, 1.02–2.16; P = .049), and TICI 2b–3 (OR, 7.11; 95% CI, 1.73–49.90; P = .017) as independent predictors of good outcome.CONCLUSIONS: Good outcome in patients with premorbid mRS 3 and 4 is less frequent compared with premorbid mRS 0–2. Nevertheless, about 20% of the patients return to their premorbid mRS, which may justify endovascular treatment. The most important predictor of good outcome is successful recanalization.MTmechanical thrombectomy